2022
DOI: 10.3389/fgene.2022.733164
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Repair-Related Genes Signature for Immune Infiltration and Outcome in Cervical Cancer

Abstract: Background: The mechanism of DNA damage repair plays an important role in many solid tumors represented by cervical cancer.Purpose: The purpose of this study was to explore the effect of DNA damage repair-related genes on immune function of patients with cervical cancer, and to establish and evaluate a prognosis model based on DNA damage repair-related genes.Methods: In the study, we analyzed the genes related to DNA damage and repair, and obtained two subtypes (F1 and F2). We selected two groups of samples fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…While fully considering the internal differences of their subclassifications, clustering parameters are designed to evaluate the correlation or eccentricity of different subgroups (spatial subregions). For different parameters, they represent different perspectives to evaluate the heterogeneity components within tumors, which is undoubtedly consistent with previous studies [ 36 39 ]. In addition to the absolute characterization of tumors, we pay attention to the direct internal relations of different subregions, and their ability to respond to internal relations is stronger than direct indicators.…”
Section: Discussionsupporting
confidence: 87%
“…While fully considering the internal differences of their subclassifications, clustering parameters are designed to evaluate the correlation or eccentricity of different subgroups (spatial subregions). For different parameters, they represent different perspectives to evaluate the heterogeneity components within tumors, which is undoubtedly consistent with previous studies [ 36 39 ]. In addition to the absolute characterization of tumors, we pay attention to the direct internal relations of different subregions, and their ability to respond to internal relations is stronger than direct indicators.…”
Section: Discussionsupporting
confidence: 87%
“…Zhu et al identified two subtypes of HPV + CC based on the most varied 50 genes across CC samples 8 . Furthermore, an increasing number of studies have identified molecular units (including DNA, RNA, and proteins) as biomarkers for the diagnosis and treatment of CC [9][10][11] . But these studies were based on bulk sequencing data, thus overlooking the extensive cellular heterogeneity of CC.…”
mentioning
confidence: 99%
“…The observed enrichment in immune-related gene sets most likely implies a primary role of interferon-dependent and other innate immunity mechanisms, which could be elicited by genomic instability and, in turn, could foster the adaptive immunity arm with tumor progression. Similarly, a marked up-regulation of innate immunity pathways (such as DNA sensormediated or interferon-induced), along with DDR "heating-up" the immune TME, has been evidenced by other researchers who explored transcriptomic profiles of more advanced CeCa stages using publicly available databases [7,12,13].…”
Section: иммунофенотип рака шейки матки ранних стадийmentioning
confidence: 90%